2019
DOI: 10.1021/acs.joc.9b01015
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Fused Carbatriphyrins(2.1.1) and Its Organo Phosphorus(V) Complex

Abstract: The first examples of phlorin analogues of meso-fused carbatriphyrins(2.1.1) and organo P­(V) complex of one of the meso-fused carbatriphyrins were obtained by adopting a premodification strategy starting with fluorene as a fused polyaromatic precursor over a sequence of steps. The meso-fused carbatriphyrins(2.1.1) were obtained as their nonaromatic phlorin analogues owing to the unstable nature of the fully conjugated meso-fused carbatriphyrins(2.1.1). The organo P­(V) complex of one of the meso-fused carbatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…There are few recent reports on PAH embedded porphyrinoids in which two adjacent pyrrole rings were replaced with different polyaromatic hydrocarbons/heterocycles such as phenanthroline, [24,25] phenanthrene, [11,12,26] bipyridine, [14] biphenyl, [15] dibenzofuran/thiophene, [27] benzofuran/ thiophene [16] and fluorene moieties. [28,29] We classified these porphyrinoids as contracted porphyrinoids. Naruta and coworkers synthesized 1,10-phenanthroline embedded porphyrins 32 a-d and used as a Mg 2 + ion sensor (Scheme 6).…”
Section: B Porphyrinoids With Two Adjacent Pyrrole Rings Substitutedmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few recent reports on PAH embedded porphyrinoids in which two adjacent pyrrole rings were replaced with different polyaromatic hydrocarbons/heterocycles such as phenanthroline, [24,25] phenanthrene, [11,12,26] bipyridine, [14] biphenyl, [15] dibenzofuran/thiophene, [27] benzofuran/ thiophene [16] and fluorene moieties. [28,29] We classified these porphyrinoids as contracted porphyrinoids. Naruta and coworkers synthesized 1,10-phenanthroline embedded porphyrins 32 a-d and used as a Mg 2 + ion sensor (Scheme 6).…”
Section: B Porphyrinoids With Two Adjacent Pyrrole Rings Substitutedmentioning
confidence: 99%
“…Ravikanth and co-workers synthesized the phlorin analog of meso-fused carbatriphyrins(2.1.1) 71 a-b and the fully conjugated aromatic macrocycle of phosphorus(V) complex of one of the phlorin analog 71 a.P as shown in Scheme 17. [28] The fluorene was subjected to Friedel-Crafts benzoylation to afford mono-benzoylated fluorenes 28 a-b which were reduced with NaBH 4 in THF/CH 3 OH at room temperature to the corresponding mono-ols 72 a-b. The mono-ols 72 a-b were treated with n-BuLi in THF followed by 2-thiophenecarboxaldehyde at 0°C to afford corresponding diols 73 a-b in 55-60% yields.…”
Section: B Porphyrinoids With Two Adjacent Pyrrole Rings Substitutedmentioning
confidence: 99%
See 1 more Smart Citation
“…The aromatic 2‐oxypyritriphyrin(1.2.1) 2 in freebase form was just reported by Neya and co‐workers by introducing 3‐pyridone moiety in the macrocyclic core and validated its redox interconversion properties [5] . On the other hand, the carba‐analogues of triphyrins are barely reported [6] . The carbatriphyrin 3 with azulene unit as part of the macrocyclic framework was reported by Latos‐Grażyński and co‐workers and spectrally characterized organo‐Ru(II) complex [7] .…”
Section: Figurementioning
confidence: 94%
“…In 2019, Ravikanth et al reported meso -fused carbatriphyrins(2.1.1) based on a fused fluorene motif ( Scheme 371 ). 716 Condensation of pentafluorobenzaldehyde and the fluorene-based tripyrranes 371.1a , b produced the phlorin-like 371.2a , b rather than the expected fully conjugated 371.3a . However, the phosphorus(V) complex 371.4a was obtained in 48% yield by treating the phlorin 371.2a with PCl 3 in toluene/triethylamine.…”
Section: Macrocyclic Systemsmentioning
confidence: 99%